Organisasi Dan Desain Pengembangan Kurikulum Pendidikan Agama Islam Pada MI Terpadu Mutiara Assyifa - Friti Sulastri (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to analyze the Organization and Design of Islamic Religious Education Curriculum Development at MI Terpadu Mutiara Assyifa. This study uses a qualitative research type. The results of the study: The organization and design of the Islamic Religious Education curriculum at MI Mutiara Assyifa used by teachers of the Al-Qur'an Hadith, Fiqh, SKI, and Akidah Akhlak, use the independent learning curriculum with a differentiated learning design. The implementation of this independent learning is expected to enable students to think critically and wisely in determining attitudes, as well as understanding and applying the values of Islamic teachings in everyday life. The types of differentiated learning applied are content differentiation, process differentiation, and product differentiation which are always applied by teachers during the teaching and learning process both in and outside the classroom. Differentiated Design can provide opportunities for students to choose topics, can develop learning skills, and encourage students to be able to create new products in the learning process.